Tinjauan Terhadap Pelaku Tindak Pidana dalam Pembuktian Dilihat dari Perkspektif Psikologi Forensik - Hasan Alzagladi; Agastia Irdrananda (Rechtsregel : Jurnal Ilmu Hukum, 2021)
One branch of forensic science that used in diagnosing perpetrators, personality, and psychological problems is forensic psychology. In forensic psychology, there is a psychological theory approach that aims to analyze the motives for criminal behavior. Some of the psychological theories in question are social learning theories and mental disorders. With a matter of manner or personality, the performance of perpetrators of criminal acts or prisoners will certainly not be the same because they are working with different aspects in the deal with certain conditions. The performance of prisoners divided into three stages, namely the behavior of the prisoner before being sentenced, the behavior of the prisoner when sentenced, and the behavior of the prisoner after being punished.